2023
DOI: 10.3390/jof9030336
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Fusarium Wilt in Watermelon by Bacillus amyloliquefaciens DHA55 through Extracellular Production of Antifungal Lipopeptides

Abstract: Fusarium wilt caused by Fusarium oxysporum f. sp. niveum is one of the most devastating fungal diseases affecting watermelon (Citrullus lanatus L.). The present study aimed to identify potent antagonistic bacterial strains with substantial antifungal activity against F. oxysporum f. sp. niveum and to explore their potential for biocontrol of Fusarium wilt in watermelon. Out of 77 isolates from watermelon rhizosphere, six bacterial strains—namely, DHA4, DHA6, DHA10, DHA12, DHA41, and DHA55—exhibited significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 82 publications
1
40
0
Order By: Relevance
“…The study identified 2-nonanone and 2-heptanone as the most potent antifungal VOCs, with acetoin and 2,3-butanediol acting as growth promoters in a dose-dependent manner [ 41 ]. Additionally, Al-Mutar et al (2023) reported that B. amyloliquefaciens DHA55 displayed antifungal activity against Fon and other phytopathogenic fungi, mediated by the production of lipopeptides such as iturin, surfactin, and fungycin [ 63 ].…”
Section: The Importance and Applications Of The Bacillus Am...mentioning
confidence: 99%
“…The study identified 2-nonanone and 2-heptanone as the most potent antifungal VOCs, with acetoin and 2,3-butanediol acting as growth promoters in a dose-dependent manner [ 41 ]. Additionally, Al-Mutar et al (2023) reported that B. amyloliquefaciens DHA55 displayed antifungal activity against Fon and other phytopathogenic fungi, mediated by the production of lipopeptides such as iturin, surfactin, and fungycin [ 63 ].…”
Section: The Importance and Applications Of The Bacillus Am...mentioning
confidence: 99%
“…Therefore, the academic community has now turned to biological control methods, and some members of the Bacillus genus have been developed and found to be effective in controlling Fusarium wilt. Therefore, they have the potential to replace chemical fungicides to avoid their harmful effects . Previous reports have shown that the antifungal activity of Bacillus strains is mainly attributed to the secretion of bioactive lipopeptides, which have attracted great interest in the agricultural community due to their unique properties, including nontoxicity, stability, and broad-spectrum antimicrobial activities …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they have the potential to replace chemical fungicides to avoid their harmful effects. 2 Previous reports have shown that the antifungal activity of Bacillus strains is mainly attributed to the secretion of bioactive lipopeptides, which have attracted great interest in the agricultural community due to their unique properties, including nontoxicity, stability, and broad-spectrum antimicrobial activities. 3 Lipopeptides are synthesized by nonribosomal peptide synthetase pathways in Bacillus species and are classified into three main families of iturins, fengycins, and surfactins based on their structural features and sequence variations.…”
Section: Introductionmentioning
confidence: 99%
“…These are known to inhibit the growth of fungi and bacteria or induce systemic resistance in host plants [11][12][13][14]. Polyketides and other antibiotics (bacilysin and bacteriocin) exhibit strong bactericidal activity against fungi, bacteria, and algae [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%